2017
DOI: 10.15252/emmm.201707561
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of γ‐secretases leads to accumulation of substrates and non‐Alzheimer neurodegeneration

Abstract: Abstractγ‐Secretases are a family of intramembrane cleaving aspartyl proteases and important drug targets in Alzheimer's disease. Here, we generated mice deficient for all γ‐secretases in the pyramidal neurons of the postnatal forebrain by deleting the three anterior pharynx defective 1 (Aph1) subunits (Aph1abc cKO Cre +). The mice show progressive cortical atrophy, neuronal loss, and gliosis. Interestingly, this is associated with more than 10‐fold accumulation of membrane‐bound fragments of App, Aplp1, Nrg1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…Previous studies have suggested that intraneuronal accumulation of APP-CTF is a consequence of impaired lysosomal-autophagic degradation, rather than a cause of endolysosome or autophagy dysfunction ( Peric and Annaert, 2015 ). In addition, a recent study showed that deletion of APP expression in mice deficient for all γ-secretases, by deletion of the genes encoding Aph1 subunits, failed to rescue progressive neurodegeneration ( Acx et al., 2017 ). In that case, there was a general accumulation of many γ-secretase substrates, due to complete loss of γ-secretase function, which is in contrast to the hypomorphic character of autosomal dominant pathogenic mutations in PSEN1 ( Moore et al., 2015 , Chávez-Gutiérrez et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that intraneuronal accumulation of APP-CTF is a consequence of impaired lysosomal-autophagic degradation, rather than a cause of endolysosome or autophagy dysfunction ( Peric and Annaert, 2015 ). In addition, a recent study showed that deletion of APP expression in mice deficient for all γ-secretases, by deletion of the genes encoding Aph1 subunits, failed to rescue progressive neurodegeneration ( Acx et al., 2017 ). In that case, there was a general accumulation of many γ-secretase substrates, due to complete loss of γ-secretase function, which is in contrast to the hypomorphic character of autosomal dominant pathogenic mutations in PSEN1 ( Moore et al., 2015 , Chávez-Gutiérrez et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…γ-Secretases are a family of intramembrane cleaving aspartyl proteases, consisting of four subunits presenilin (PSEN), anterior pharynx defective-1, nicastrin, and presenilin enhancer-2 [ 41 ]. When the expression and activity of those four subunits were changed, the catalytic function of γ-secretases could also be changed [ 42 ]. Recent evidence showed that rats fed with Res, a SIRT1 inducer, exhibit a significant increase in PSEN1 expression, which is one of SIRT1-specific DNA targets [ 26 ].…”
Section: Effect Of Res On Aβ Productionmentioning
confidence: 99%
“…PS1 (467 aa; 46 kDa) and PS2 (448 aa; 55 kDa) share 66.3% sequence identity (with a sequence similarity of 71.9%) at the amino acid level; both harbor the two conserved catalytic aspartic acid residues, Asp-263 and Asp-366 (PS2 numbering), and are involved in a variety of biological processes. [31][32][33][34] PS2 is located predominantly within the endoplasmic reticulum (ER) and early Golgi apparatus and is primarily expressed in neurons, whereas PS1 associates mainly with cell membranes. 35 To reach a mature active state, both proteins are proteolytically autocleaved to generate two chains, the N-terminal and Cterminal fragments (NTF and CTF).…”
Section: Introductionmentioning
confidence: 99%